The Influence of Live Streaming on Purchase Decisions through Purchase Interest as A Mediation for Fashion Products in Tiktok Shop - Siti Saadah; Rahyuniati Setiawan; Gita Garliani (Manunggal Halim Jaya, 2026)
The development of social commerce in Indonesia, particularly the TikTok Shop platform, has transformed how fashion businesses market their products through live streaming features (pp. 1, 14). This study aims to analyze the effect of live streaming on purchasing decisions, both directly and indirectly through purchase intention as a mediating variable for fashion products on TikTok Shop (pp. 1, 20). The research method used is a quantitative approach with descriptive and verification methods (p. 7). Data collection was conducted by distributing questionnaires to TikTok Shop users in Indonesia (pp. 7, 11). The data analysis technique employed in this study is Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the structural relationships between variables (p. 7). Descriptive analysis results are used to determine the general overview of live streaming, purchase intention, and purchasing decision variables (pp. 7, 20). Through outer model and inner model analysis, this study evaluates validity, reliability, and both direct and indirect effects between variables (pp. 8-9). The hypothesis testing results are expected to prove the significant contribution of live streaming in stimulating consumer purchase intention, which ultimately drives the actual action of making a purchasing decision for fashion products (pp. 8, 19). This study provides practical contributions for TikTok Shop sellers in designing more effective interactive digital marketing strategies.